Efficacy of Cinnamomum cassia essential oil against food-borne molds and aflatoxin B1 contamination. (27th May 2021) - Singh, Akanksha; Deepika,; Chaudhari, Anand Kumar; Das, Somenath; Prasad, Jitendra; Dwivedy, Abhishek Kumar; Dubey, Nawal Kishore
Abstract: The present study deals with the antifungal and antiaflatoxigenic potential of Cinnamomum cassia essential oil (CCEO) against aflatoxigenic food borne Aspergillus flavus strain (AF-LHP-PE-4), and probable mode of action including the safety profile on male mice. CCEO completely inhibited fungal growth and aflatoxin B1 secretion at its minimum inhibitory concentration (0.06 µL/mL). CCEO inhibited ergosterol biosynthesis in cell membranes and also disturbed the membrane fluidity. Significant enhancement in leakage of cellular ions and 260 and 280 nm absorbing cellular materials in response to increased concentrations of CCEO indicated the plasma membrane as the probable site of antifungal toxicity. The antiaflatoxigenic potency of CCEO was confirmed in terms of reduction in the level of cellular methylglyoxal (MG), the inducer of aflatoxin. Antioxidant activity of CCEO was confirmed through DPPH free radical scavenging activity as well as total phenolic content. Chemical profiling of CCEO by gas chromatography-mass spectrometry (GC-MS) analysis revealed the presence of cinnamaldehyde (84.01%) as the most abundant compound. CCEO exhibited a high LD50 (10410.75 µL/kg) on male mice, strengthening its favorable safety profile. This is the first report on CCEO as novel green preservative against food storage molds and aflatoxin B1 secretion.